Macroeconomic influences on price fluctuations of basic goods in Finland from 2016 to 2023 - Lindevall, Alex (My University, 2024)
Food prices in the Finnish market are strongly represented due to global challenges. Inflation is rising, which is reflected in higher prices of consumer goods. Due to inflation, consumers' purchasing power has decreased, and the increased prices of everyday food products are reflected in the price of the shopping cart. The study is based on price developments in 2016- 2023, and over the years, there have been two more significant factors whose impact has been evident in the global market. This study examines how macroeconomic changes have affected the price of the consumer's food basket. The data used for the study are Statistics Finland's Consumer Price Index, the general level of inflation, and the annual price basket comparison of Helsingin Sanomat. The study also examines how the pricing of the three largest operators in the Finnish grocery trade has developed in the changing market situation. The analysis offers a comprehensive overview of price dynamics within these product categories over the specified period, providing valuable insights into inflationary trends and consumer price behavior in Finland. This research contributes to a broader understanding of economic conditions and consumer price sensitivity.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development